2011
DOI: 10.1007/s11060-011-0613-6
|View full text |Cite
|
Sign up to set email alerts
|

Modern management of rare brain metastases in adults

Abstract: Brain metastases (BM) represent the main cause of intracranial neoplasms in adults, while being relatively less common in children. Today, better treatment options of the primary malignancy lead to higher remission rates as well as prolonged stable clinical conditions. This may in part explain the increased incidence of BM. Morbidity and mortality rates in patients with malignancies deteriorate significantly in cases of metastatic involvement of the central nervous system. Nowadays, especially modern managemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 123 publications
(215 reference statements)
0
4
0
Order By: Relevance
“…In the present study, peripherally enhanced thin cyst walls (37/62, 59.7%) were more frequently observed compared to other common metastatic brain tumors. In Table 4, imaging features of brain metastases associated with esophageal carcinomas that have been published since 2004 [2,[11][12][13][14][15][16][17][18][19] are presented. In particular, cystic, enhanced tumors with minimal edema were notable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, peripherally enhanced thin cyst walls (37/62, 59.7%) were more frequently observed compared to other common metastatic brain tumors. In Table 4, imaging features of brain metastases associated with esophageal carcinomas that have been published since 2004 [2,[11][12][13][14][15][16][17][18][19] are presented. In particular, cystic, enhanced tumors with minimal edema were notable.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8]11,16] However, the majority of esophageal carcinoma reports were still based on autopsies. [9,10] With the clinical application of MRI, a larger number of reports of esophageal carcinoma have been published, [2][3][4][12][13][14][15][17][18][19] although, few reports have described both MRI findings and clinical features. Worldwide, the incidence of brain metastases from esophageal carcinoma ranges from 0.3% to 13%.…”
Section: Introductionmentioning
confidence: 99%
“…It is still an evolving area of cancer care. Very few studies have further reported about treatment of rare brain metastases [15]. Our study focuses on surgical treatment of eloquent region metastases arising from unusual primary malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…There is paucity of literature regarding management of eloquent area metastases arising from rare primary malignancies [15]. We present our experience after surgery for 10 consecutive patients harbouring eloquent area metastasis from rare primary malignancies to illustrate the safety and effectiveness of microsurgical resection leading to good early outcome.…”
Section: Introductionmentioning
confidence: 99%